Introducing blended learning and course design to adult learners hard-to-reach - Lencastre, José Alberto (2019)
Adult trainers often find themselves redesigning curriculum, exploring new pedagogical approaches, and seeking stimulating changes to their courses, especially when working with hard-to-reach groups. This paper introduces blended learning and course design to adult learners hard-to-reach. The article also highlights data on best practices when looking for training with heterogeneous audiences with difficulties in the basic knowledge of a foreign language. We begin with actual questionnaire data for refugee women regarding their educational needs and learning materials to propose the design and the teaching approach of a blended learning course. We succinctly explain online approaches, compares pedagogy styles and learning theories with a focus on women's knowledge, and compare traditional education to blend instruction. From this article, trainers can expect to learn: (i) the concept of blended learning; (ii) ideas for designing blended teaching experiences; and (iii) data-driven justification for blend teaching in an adult course.